2021
DOI: 10.3390/medicina57040360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Activity on Disability Risk in Elderly Patients Hospitalized for Mild Acute Diverticulitis and Diverticular Bleeding Undergone Conservative Management

Abstract: Background and Objectives: The role of physical activity (PA) in elderly patients admitted to surgical units for mild acute diverticulitis in the development of disability has not been clarified so far. Our aim is to demonstrate the relationship between physical activity and better post-discharge outcomes on disability in elderly population affected by diverticular disease. Materials and Methods: We retrospectively reviewed data of 56 patients (32 Males-24 females) collected from October 2018 and March 2020 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…As PA declines, seniors are at risk for cognitive decline. Of our proband group, 58% were also at risk of cognitive decline due to the avoidance of regular PA. Social services using personal devices that measure PALs could identify users at risk through long-term assessment of PAL and alert them to the health risks associated with low PA, such as diverticulitis [ 33 ]. It is essential to address methods of motivating regular activity during periods of isolation.…”
Section: Discussionmentioning
confidence: 99%
“…As PA declines, seniors are at risk for cognitive decline. Of our proband group, 58% were also at risk of cognitive decline due to the avoidance of regular PA. Social services using personal devices that measure PALs could identify users at risk through long-term assessment of PAL and alert them to the health risks associated with low PA, such as diverticulitis [ 33 ]. It is essential to address methods of motivating regular activity during periods of isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, also comorbidities prevalence, like hypertension, COPD, and cardiovascular diseases, are higher in our population due to older patients [34][35][36].…”
Section: Discussionmentioning
confidence: 95%
“…Accumulation of health deficits related to functional status, mobility, malnutrition, and comorbidities are all elements of frailty, apart from the chronological age, which may influence the overall survival [53]. Poor physical performance is strongly associated with disability and adverse surgical outcomes [54,55]. A meta-analysis study revealed that sarcopenia was associated with an increased risk of complications after gastrointestinal tumor resection and suggested that combination of physical performance and muscle mass measurements may increase the prognostic value and accuracy in preoperative risk stratification [47].…”
Section: Discussionmentioning
confidence: 99%